2015
DOI: 10.1521/jscp.2015.34.2.135
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Relational Aggression and Internalizing Symptoms: A Review and Meta-Analysis

Abstract: Relational aggression is associated with negative psychosocial consequences, but more information is needed about connections between relational aggression and other problems. this review and meta-analysis examines the association between relational aggression and internalizing symptoms in 24,622 children between the ages of 5 and 17 years old, gathered from 42 studies. In addition to evaluating the overall relation between these constructs, this review examines the state of the literature with respect to six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…From a theoretical standpoint, fears about social interactions might magnify one's existing decreased ability to understand another's perspective or internalize another's emotions in situations of social distress. Among older adolescents, social anxiety has been related to risk-avoidant decision making (Maner et al, 2007). Therefore, for socially anxious adolescents, lower empathy levels might be more strongly associated with covert types of aggression (such as indirect or cyber aggression) compared to adolescents low on social anxiety.…”
Section: Social Anxiety: a Potential Moderatormentioning
confidence: 99%
“…From a theoretical standpoint, fears about social interactions might magnify one's existing decreased ability to understand another's perspective or internalize another's emotions in situations of social distress. Among older adolescents, social anxiety has been related to risk-avoidant decision making (Maner et al, 2007). Therefore, for socially anxious adolescents, lower empathy levels might be more strongly associated with covert types of aggression (such as indirect or cyber aggression) compared to adolescents low on social anxiety.…”
Section: Social Anxiety: a Potential Moderatormentioning
confidence: 99%
“…However, the above-mentioned conclusions are unequivocal: There are studies that have revealed non-significant correlations between gender and workplace aggression (e.g., Douglas & Martinko, 2001;Inness, Barling, & Turner, 2005), including circumstances in which gender was included as the control variable and consequently dropped from the analyses, given the non-significant relations with workplace deviance (e.g., Biron, 2010). Accordingly, a meta-analysis of workplace aggression conducted by Hershcovis et al (2007) indicated that there is little gender difference with respect to indirect forms of aggression (e.g., spreading rumors, damaging property, acts of verbal aggression, and giving ''dirty looks''; see Marshall, Arnold, Rolon-Arroyo, & Griffith, 2015;Richardson, 2014 for formulizations of ''direct'' and ''indirect'' aggression).…”
Section: Introductionmentioning
confidence: 99%
“…However, while these comparisons provide information on the magnitude of a general tendency of each gender to behave in certain way (and indicate whether any differences in these tendencies are statistically significant), they led only to rough distinctions but did not provide data regarding the prevalence of more specific behavioral manifestations (see Bjorkqvist et al, 1994;Kogut et al, 1992;Meyers-Levy & Loken, 2015). Since the previous gender differences studies were based on overall or average measure of verbal and physical aggression (e.g., Marshall, et al, 2015) or of direct and indirect aggressive behaviors (e.g., Warren et al, 2011), not a specific measure of them, it would not be possible to identify which subscales or items (included in the mean score) are responsible for gender differences.…”
Section: Perfiles De Género De Desviación Individual Y Organizacionalmentioning
confidence: 99%